ANALISIS KEMAMPUAN KONEKSI MATEMATIK DAN KEPERCAYAAN DIRI SISWA SMP - DIAN Andriani; Usman Aripin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to determine the mathematical connection skills and confidence of junior high school students. With the background of the low mathematical connection skills and self-confidence of students, this study was conducted. The method used for analysis in this study is a Descriptive Qualitative Method that aims to be able to analyze the results of students 'work on the questions of students' mathematical connection abilities and questionnaires to search for confidence in students of SMP Bina Harapan Bangsa. The subjects studied were 1 class of students, amounting to 37 students in class IX-B of Bina Harapan Bangsa Middle School in Bandung Regency. The test questions used are mathematical connections with the questions given as many as 3 questions and non-test instruments for students' self-confidence. The results of the analysis obtained are the mathematical connection ability of students in junior high schools in the district of Bandung based on written description tests are still relatively low. But students already have good confidence in learning mathematics.